In-Situ Wireless Pressure Measurement Using Zero-Power Packaged Microwave Sensors - Julien Philippe; Maria Valeria De Paolis; Dominique Henry; Alexandre Rumeau; Antony Coustou; Patrick Pons; Hervé Aubert (Sensors, 2019)
This paper reports the indoor wireless measurement of pressure from zero-power (or passive) microwave (24 GHz) sensors. The sensors are packaged and allow the remote measurement of overpressure up to 2.1 bars. Their design, fabrication process and packaging are detailed. From the measurement of sensor scattering parameters, the outstanding sensitivity of 995 MHz/bar between 0.8 and 2.1 bars was achieved with the full-scale measurement range of 1.33 GHz. Moreover, the 3D radar imagery technique was applied for the remote interrogation of these sensors in electromagnetic reverberant environments. The full-scale dynamic range of 4.9 dB and the sensitivity of 4.9 dB/bar between 0.7 and 1.7 bars were achieved with radar detection in a highly reflective environment. These measurement results demonstrate for the first time the ability of the radar imagery technique to interrogate fully passive pressure sensors in electromagnetic reverberant environments.